Bionic artificial skin with a fully implantable wireless tactile sensory system for wound healing and restoring skin tactile function - Kyowon Kang; Seongryeol Ye; Chanho Jeong; Jinmo Jeong; Yeong-sinn Ye; Jin-Young Jeong; Yu-Jin Kim; Selin Lim; Tae Hee Kim; Kyung Yeun Kim; Jong Uk Kim; Gwan In Kim; et al. (Nature Communications, 2024)
Abstract Tactile function is essential for human life as it enables us to recognize texture and respond to external stimuli, including potential threats with sharp objects that may result in punctures or lacerations. Severe skin damage caused by severe burns, skin cancer, chemical accidents, and industrial accidents damage the structure of the skin tissue as well as the nerve system, resulting in permanent tactile sensory dysfunction, which significantly impacts an individual’s daily life. Here, we introduce a fully-implantable wireless powered tactile sensory system embedded artificial skin (WTSA), with stable operation, to restore permanently damaged tactile function and promote wound healing for regenerating severely damaged skin. The fabricated WTSA facilitates (i) replacement of severely damaged tactile sensory with broad biocompatibility, (ii) promoting of skin wound healing and regeneration through collagen and fibrin-based artificial skin (CFAS), and (iii) minimization of foreign body reaction via hydrogel coating on neural interface electrodes. Furthermore, the WTSA shows a stable operation as a sensory system as evidenced by the quantitative analysis of leg movement angle and electromyogram (EMG) signals in response to varying intensities of applied pressures.